A Simulation Study of Service Differentiation for the Bandwidth Request Scheme in Fixed IEEE 802.16 Network - 周异 齐开悦 陈剑波 陈凯 何建华 (Shanghai jiao tong da xue xue bao, 2009)
Various flexible mechanisms related to quality of service （QoS） provisioning have been specified for uplink traffic at the medium access control （MAC） layer in the IEEE 802.16 standards. Among the mechanisms, contention based bandwidth request scheme can be used to indicate bandwidth demands to the base station for the non-real-time polling and best-effort services. These two services are used for most applications with unknown traffic characteristics. Due to the diverse QoS requirements of those applications, service differentiation （SD） is anticipated over the contention based bandwidth request scheme. In this paper we investigate the SD with the bandwidth request scheme by means of assigning different channel access parameters and bandwidth allocation priorities at different packets arrival probability. The effectiveness of the differentiation schemes is evaluated by simulations. It is observed that the initial backoff window can be efficient in SD, and if combined with the bandwidth allocation priority, the SD performances will be better.